‘HEAR’ IT LOUD AND CLEAR - Parkash, Parveen (SCHOOL SCIENCE, 2013)
Loss of hearing is one of the largest yet least defined ailments in India. Statistics show that one out of every 12 persons in this country is affected by this problem to some degree. Yet we pay less attention to hearing loss. Perhaps, this is because hearing loss is invisible and painless. In fact, those who are deaf suffer from devastating emotional, social and psychological pain. Hearing loss is India’s least understood problem because it is a hurt that does not show. Among the infirm and defective, the deaf mutes are most short - lived as they suffer in silence, are less expressive and the least understood. Today, there are many unsolved problems related to hearing and balance disorders, and there are indications that the size of the problem is growing. Though the opportunities to do something about these problems today are better than ever before, the many unsolved mysteries of hearing and balance disorders still persist. Poor hearing disrupts communication among people. Most important among them is between teachers and students and father or mother and children. It leads to falling grades, isolation and unhappiness among learners. Hearing loss among olds leads to strained tempers and irritability. Aged persons should take degeneration of ears sportingly and get their hearing tested with the help of audiometry tests after which suitable hearing aid can be used. Emotional stress which accompanies hearing loss in children, young ones and elderly can be reduced through awareness, motivation, rehabilitation and planning